Inflation persistence - Jeffrey C. Fuhrer (Federal Reserve Bank of Boston, 2009)
This paper examines the concept of inflation persistence in macroeconomic theory. It begins with a definition of persistence, emphasizing the difference between reduced]form and structural persistence. It then examines a number of empirical measures of reduced]form persistence, considering the possibility that persistence may have changed over time. The paper then examines the theoretical sources of persistence, distinguishing gintrinsich from ginheritedh persistence, and deriving a number of analytical results on persistence. It summarizes the implications for persistence from the literatures on gsticky]informationh models, learning models, and so]called gtrend inflation models,h providing some new results throughout.
Keywords: G1; G3; 330; Inflationsrate; Phillips-Kurve; Autokorrelation; Schätzung; USA